Utilizing information technology in developing strategic alliances among organizations - Martinez-Fierro, Salustiano, 1973-; Medina Garrido, José Aurelio.; Ruiz Navarro, José. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This book deals with two important topics for a firm's competitiveness in the framework of the information society: alliance strategies and the role played by IT in alliances. While technical solutions to distance work abound, there is a lack of a strong and theoretically-grounded approach on how best to implement these solutions. The book offers a theoretical framework, allowing strategic alliance managers to implement the IT required in these alliances, supported by their work teams. This book analyzes many important topics, such as: the development of global business-to-business electronic markets, and whether these markets are becoming a way of improving trust between organizations at an international level; problems in implementing interorganizational systems and their solutions; and how IT and alliance strategy are important both to multinational corporations and family firms, regardless of firm size.